2011
DOI: 10.1111/j.1468-2370.2011.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Venture Capital Syndication: Synthesis and future directions

Abstract: This paper reviews and synthesizes the extant literature on venture capital syndication. By considering the questions of how, why, and when syndication affects the performance of VC firms and their portfolio ventures, we form a schematic structure of the syndication literature and identify areas for further research. The results of the review show that while the venture-level aspects are relatively well understood, the current literature lacks an understanding of how and why syndication affects the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 137 publications
(341 reference statements)
2
22
0
1
Order By: Relevance
“…

Risk aversion explains much of the structure of interfi rm cooperation.

Being well connected explains outperformance.

Venture capital fi rms benefi t from syndication with a range of successful peers. Similar fi gures have been observed for the US VC market (Gompers and Lerner, 2001;Jääskeläinen, 2011). capital fi rms co-invest in a venture, they defi ne an interfi rm tie of cooperation between them.

…”
supporting
confidence: 74%
“…

Risk aversion explains much of the structure of interfi rm cooperation.

Being well connected explains outperformance.

Venture capital fi rms benefi t from syndication with a range of successful peers. Similar fi gures have been observed for the US VC market (Gompers and Lerner, 2001;Jääskeläinen, 2011). capital fi rms co-invest in a venture, they defi ne an interfi rm tie of cooperation between them.

…”
supporting
confidence: 74%
“…; Cornelli and Yosha ; Cumming ,b, , ; Gompers ; Gompers et al . ; Hirsch and Walz ; Jääskeläinen ; Jääskeläinen et al . ; Kaplan and Strömberg ; Krohmer et al .…”
Section: Vc Contract and Security Designunclassified
“…In the literature, the ventures' performance is usually presented with the successful exit option or the internal rate of return (IRR) and VC syndication generally views this positively (Jääskeläinen, 2012). Brander et al (2002) investigated 584 VC exits in the US and found that the syndicated ventures enjoy significantly higher return compared to the rest.…”
Section: Syndication Decisionmentioning
confidence: 99%
“…Investment syndication in the venture capital market is fairly common with some regional variations. For example, almost one third of the European VC investments and around two thirds for the US venture investments are syndicated (Manigart et al, 2006;Jääskeläinen, 2012). Bygrave (1987) in his pioneering work on VC syndication argued that uncertainty associated with investment and need to access the specialised resources of other investors primarily drive syndication.…”
Section: Syndication Decisionmentioning
confidence: 99%